2015
DOI: 10.1096/fj.14-263889
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNAs as a novel component of the Myc transcriptional network

Abstract: Myc is a well-known transcription factor with important roles in cell cycle, apoptosis, and cellular transformation. Long noncoding RNAs (lncRNAs) have recently emerged as an important class of regulatory RNAs. Here, we show that lncRNAs are a main component of the Myc-regulated transcriptional program using the P493-6 tetracycline-repressible myc model. We demonstrate that both Myc-induced mRNAs and lncRNAs are significantly enriched for Myc binding sites. In contrast to Myc-repressed mRNAs, Myc-repressed lnc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
59
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 49 publications
2
59
0
Order By: Relevance
“…The promoters of many lncRNAs are bound and regulated by transcription factors known to influence mRNA transcription, including cancer-related transcription factors, such as p53 [15, 16], Myc [17, 18] and E2F [1922]. …”
Section: Introductionmentioning
confidence: 99%
“…The promoters of many lncRNAs are bound and regulated by transcription factors known to influence mRNA transcription, including cancer-related transcription factors, such as p53 [15, 16], Myc [17, 18] and E2F [1922]. …”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies on c-Myc's transcriptional network have mainly focused on protein-coding genes, it has been increasingly recognized that c-Myc is also capable of regulating noncoding RNAs (26). These include both microRNAs (miRNAs) and long noncoding RNAs (lncRNAs) (27)(28)(29)(30)(31)(32)(33)(34)(35). The lncRNAs are defined as non-protein-coding RNA transcripts longer than 200 nucleotides (nt) (36).…”
mentioning
confidence: 99%
“…MYC is a transcription factor involved in cell growth, proliferation and maintenance of stem cell-like properties 3,4 . Besides protein-coding genes, MYC also regulates the expression of multiple microRNAs (miRNAs) and long non-coding (lnc)RNAs 5,6 . In a previous study 7 , we identified a MYC-related miRNA expression profile in pediatric BL as compared to MYC-low chronic lymphocytic leukemia (CLL).…”
mentioning
confidence: 99%